Reciprocal teaching strategy to improve students’ reading comprehension - Díaz Chávez, Ana Paula (2022)
Reading is considered the most important skill in teaching and learning English, reason for all the other skills are developed through reading, which means that without reading, there is not speaking, without speaking there is not listening, in consequence, without listening there is not writing. The main objective of this research is to explain the incidence of the reciprocal teaching strategy to improve reading comprehension of High School students at Unidad Educativa “Academia Naval Cap. Leonardo Abad Astudillo”. Also, the methodology applied in this research was purely quantitative with a phenomenological study, where a questionnaire was applied through focus groups. The results obtained from the focus groups reflect that students have problems when they are doing reading comprehension activities, since they are not able to easily predict a text which affects their ability to summarize in their own words. Furthermore, students need to improve their reading sub-skills (encode, decode) because these are important to develop their reading comprehension. With the implementation of the reciprocal teaching, it could significantly improve the students’ reading comprehension of this institution.